Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte